Prognostic Role of MicroRNA-200c-141 Cluster in Various Human Solid Malignant Neoplasms. (18th October 2015) - Li, Xiao-yang; Li, Hui; Bu, Jie; Xiong, Liang; Guo, Hong-bin; Liu, Li-hong; Xiao, Tao
Abstract : The miR-200 family has emerged recently as a noticeable marker for predicting cancer prognosis and tumor progression. We aimed to review the evidence of miR-200c-141 genomic cluster as prognostic biomarkers in cancers. The results suggested that high level of miR-200c had no significant impact on OS (HR = 1.14 [0.77–1.69], P = 0.501 ) and DFS/PFS (HR = 0.72 [0.45–1.14], P = 0.161 ). Stratified analyses revealed that high miR-200c expression was significantly related to poor OS in serum/plasma (HR = 2.12 [1.62–2.77], P = 0.000 ) but not in tissues (HR = 0.89 [0.58–1.37], P = 0.599 ). High miR-200c expression was significantly associated with favorable DFS/PFS in tissues (HR = 0.56 [0.43–0.73], P = 0.000 ) but worse DFS/PFS in serum/plasma (HR = 1.90 [1.08–3.36], P = 0.027 ). For miR-141, we found that high miR-141 expression predicted no significant impact on OS (HR = 1.18 [0.74–1.88], P = 0.482 ) but poor DFS/PFS (HR = 1.11 [1.04–1.20], P = 0.003 ). Similarly, subgroup analyses showed that high miR-141 expression predicted poor OS in serum/plasma (HR = 4.34 [2.30–8.21], P = 0.000 ) but not in tissues (HR = 1.00 [0.92–1.09], P = 0.093 ). High miR-141 expression was significantly associated with worse DFS/PFS in tissues (HR = 1.12 [1.04–1.20], P = 0.002 ) but not in serum/plasma (HR = 0.90 [0.44–1.83], P = 0.771 ). Our findings indicated that, compared to their tissue counterparts, the expression level of miR-200c and miR-141 in peripheral blood may be more effective for monitoring cancer prognosis. High miR-141 expression was better at predicting tumor progression than survival for malignant tumors.